2020
DOI: 10.13057/biodiv/d211103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer type and harvesting age on species composition, yield and chemical composition of natural pasture in the highlands of Ethiopia

Abstract: Abstract. Yalew S, Asmare B, Mekuriaw Y. 2020. Effects of fertilizer type and harvesting age on species composition, yield, and chemical composition of natural pasture in the highlands of Ethiopia. Biodiversitas 21: 4999-5007. The experiment was conducted to evaluate the effects of fertilizer type and harvesting age on species composition, yield, and chemical composition of natural pasture in the highlands of Ethiopia. The experiment was laid out in randomized complete block design with factorial arrangement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Nemera et al (2017) reported a higher proportion of legumes under cattle manure and wood ash, which contradicts our finding. Similar to our study, Atsbha et al (2020) and Yalew et al (2020) reported a higher proportion of forbs in the unfertilized (control) treatment group. The higher proportion of grasses and the lower proportion of legumes in the second yr (see Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nemera et al (2017) reported a higher proportion of legumes under cattle manure and wood ash, which contradicts our finding. Similar to our study, Atsbha et al (2020) and Yalew et al (2020) reported a higher proportion of forbs in the unfertilized (control) treatment group. The higher proportion of grasses and the lower proportion of legumes in the second yr (see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…This might be associated with variation in soil properties, climate, and the nature of the treatments used in the experiment. Conversely, other authors ( Zewudu et al 2010 ;Yalew et al 2020 ) reported comparable dry matter yield and CP content with application of organic and inorganic fertilizers under similar agroecology. The 16.7% increase in biomass yield in the control plots was likely caused by fencing to prevent animal incursion.…”
Section: Biomass and Chemical Composition Of Forage From Pasturesmentioning
confidence: 84%
“…Similarly, natural pasture harvested during rainy season contained higher CP and lower NDF, ADF, and ADL than during dry season (Berhe, 2012; Dahir, 2016). In addition, the natural pasture harvested at an early stage of harvesting (60 d) contained higher CP and lower NDF and ADF than intermediate harvesting stages (90 d) which in turn contained higher CP and lower NDF and ADF value than late harvesting stage (120 d) (Tessema et al., 2010; Yalew, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Urea application resulted in a large proportion of grass and legumes (Tessema et al, 2010). The application of urea can increase total biomass yield, which can favor grass species over other herbaceous species due to the better response of grasses to nitrogen fertilizer (You et al, 2017;Yalew et al, 2020). The low biomass yield recorded under seasonal grazing management could be due to higher proportions of legume, sedge, and forb species than in semi-intensive pastureland management (Figure 3).…”
Section: Effects Of Management and Harvesting Stage On Pasture Biomas...mentioning
confidence: 99%